The Preaching Strategy of the Ma'had Qudsiyyah Kudus in Developing the Morals of Students - Khoirrudin, Nur; Muhyiddin, Ahmad Shofi (Riwayat: Educational Journal of History and Humanities, 2025)
Efforts to foster the morals of students must be balanced with a da'wah strategy that is in accordance with the vision and mission of the Ma'had so that students can accept and feel positive moral changes in the learning process. The da'wah strategy implemented by Ma'had Qudsiyyah adheres to old traditions and adopts new, better things (al-muhafadhotu 'ala qodimis salih wal akhdzu bil jadidil aslah). This study uses a qualitative method with a field case study approach. The results of this study indicate a positive change in morals during activities at Ma'had Qudsiyyah.